The Spirit of Xieyi (Freehand) in Chinese Meticulous Painting - Hou, Qunshan (Journal of Education and Educational Research, 2025)
Contemporary Chinese-painting studies habitually treat “meticulous” (gongbi) and “freehand” (xieyi) as two opposing camps. The former is tagged as “realistic, minute, form-oriented, polychrome, crafted, decorative, objective”; the latter as “spontaneous, bold, spirit-oriented, ink-centred, calligraphic, expressive, subjective”. Textbooks map the Tang-Song academy peak to gongbi and Yuan-Ming-Qing literati painting to xieyi, constructing a value hierarchy that privileges meaning over craft. Modern critics import the Western “representation vs. expression” binary, equating gongbi with pre-modern “representation” and xieyi with modern “expression”, thereby widening their perceived temporal and qualitative gap. Exhibition systems reinforce the split: juried shows separate “gongbi” and “xieyi”; auction houses price the former as “decorative commodity” and the latter as “academic elite”; art academies run parallel studios, funnelling students into either “technique” or “expression” tracks. The result: gongbi is expelled from the mainstream narrative, stereotyped as mere pattern-making, while xieyi, trapped in “ink-centrism”, spins into empty convention. Recent “neo-gongbi” or “gongbi-xieyi” experiments challenge the divide, yet scholarship still frames them as “binary complementarity” rather than “homologous co-birth”, unable to shake the subconscious ranking of xieyi above gongbi. This obscures the Chinese tradition of “giving form to spirit” and “advancing from craft to Dao”, and blocks gongbi from releasing its spiritual energy in a contemporary context.
Keywords: Chinese Painting; Meticulous Painting (gongbi); Spirit of Xieyi